2018
DOI: 10.12938/bmfh.17-014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of administrating polysaccharide from black currant (<i>Ribes nigrum</i> L.) on atopic dermatitis in NC/Nga mice

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease that causes dry skin and functional disruption of the skin barrier. AD is often accompanied by allergic inflammation. AD patient suffer from heavy itching, and their quality of life is severely affected. Some pharmaceuticals for AD have some side effects such as skin atrophy. So it is necessary to develop mild solutions such as food ingredients without side effects. There are various causes of AD. It is especially induced by immunological imbalances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
(27 reference statements)
1
13
0
1
Order By: Relevance
“…We obtained 13.5 g freeze-dried powder from 3,454 g blackcurrant juice; the mean MW was 27,643. This result supports the earlier result that indicates that the freeze-dried powder mainly contains fiber (16).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We obtained 13.5 g freeze-dried powder from 3,454 g blackcurrant juice; the mean MW was 27,643. This result supports the earlier result that indicates that the freeze-dried powder mainly contains fiber (16).…”
Section: Resultssupporting
confidence: 93%
“…Blackcurrant (Ribes nigrum L.) is a well-known healthy fruit that is used to prepare various foods and beverages, such as jams and juices. In previous studies, we revealed that a polysaccharide-rich substance derived from blackcurrants reduces skin inflammation linked to atopic dermatitis, and that it has an anti-tumor effect in mice (14)(15)(16). We designated this substance cassis polysaccharide (CAPS).…”
mentioning
confidence: 99%
“…Moreover, the serum IgE level in the animals treated with cassis polysaccharide at 60 mg/kg was significantly lower compared with the control group. The animals receiving the highest dose of cassis polysaccharide showed a significantly decreased number of mast cells in the epidermis [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ashigai et al. () demonstrated the effectiveness of oral intake of BC cassis polysaccharide on reducing skin dehydration caused by ultraviolet light in mice. They also reported decreases on markers of inflammation, such as those of interleukin‐6 and matrix metalloprotein transcription levels in the skin of hairless mice.…”
Section: Health Benefits Of Bioactive Compounds From Bcmentioning
confidence: 99%
“…The degraded polysaccharide U-600 W (M w = 1.32 × 10 4 kDa) ultrasound treated sample exhibited the best results for all assays performed when compared to the polysaccharide that received a lower wattage treatment. Ashigai et al (2018) demonstrated the effectiveness of oral intake of BC cassis polysaccharide on reducing skin dehydration caused by ultraviolet light in mice. They also reported decreases on markers of inflammation, such as those of interleukin-6 and matrix metalloprotein transcription levels in the skin of hairless mice.…”
Section: Health Benefits Of Bioactive Compounds From Bcmentioning
confidence: 99%